Determining factors for hemodiafiltration to equal or exceed the performance of expanded hemodialysis. Issue 10 (5th May 2020) - Maduell, Francisco; Broseta, José Jesús; Gómez, Miguel; Racionero, Pablo; Montagud‐Marrahi, Enrique; Rodas, Lida; Arias‐Guillén, Marta; Fontseré, Néstor; Vera, Manel; Rico, Nayra
Abstract: The aim of the study was to compare expanded hemodialysis (HDx) with hemodiafiltration (HDF) at different infusion flows to identify the main determinants, namely blood flow (Qb), replacement volume, infusion flow (Qi), ultrafiltration flow (Quf ), filtration fraction (FF), and the point at which the effectiveness of HDF equals or exceeds that of HDx. We conducted a prospective, single‐center study in 12 patients. Each patient underwent 12 dialysis sessions: six sessions with Qb 350 and six with Qb 400 mL/min; with each Qb, one session was with HDx and five sessions were with FX80 (one in HD, and four with Qi 50, 75, 90/100 mL/min or autosubstitution in postdilution HDF). The reduction ratios (RR) of urea, creatinine, ß2 ‐microglobulin, myoglobin, prolactin, α1 ‐microglobulin, α1 ‐acid glycoprotein, and albumin were compared intraindividually and the global removal score (GRS) was calculated. The mean replacement volume with Qb 350 mL/min was 13.77 ± 0.92 L with Qi 50 mL/min, 20.75 ± 1.17 L with Qi 75, 23.83 ± 1.92 L with Qi 90, and 27.51 ± 2.77 L with autosubstitution. Similar results were obtained with Qb 400 mL/min, and the results were only slightly higher with Qi 100 mL/min or in autosubstitution. The GRS was positively correlated with replacement volume with Qb 350 ( R 2  = 0.583) and with Qb 400 ( R 2  = 0.584); with Quf with Qb 350 ( R 2  = 0.556) and with Qb 400 ( R 2  = 0.604); and also with FF with Qb 350 ( R 2  = 0.556) and with Qb 400 mL/min ( R 2  = 0.603). The minimum convective volume in HDF from which it is possible to overcome the efficacy of HDx was 19.2 L with Qb 350 and 17.6 L with Qb 400 mL/min. The cut‐off point of Quf at which HDF exceeded the effectiveness of HDx was 80.6 mL/min with Qb 350 and 74.1 mL/min with Qb 400 mL/min. The cut‐off point at which FF in HDF exceeded the effectiveness of the HDx was 23.0% with Qb 350 and 18.6% with Qb 400 mL/min. In conclusion, this study confirms the superiority of postdilution HDF over HDx when replacement volume, convective volume, Quf, or FF exceeds certain values. Increasing the Qb in postdilution HDF manages to increase the convective dose and more easily overcome the HDx.